Analysis of overcurrent protection relay settings of a commercial building - Nurul Syaqirah, Mohd Sufi (2016)
This paper presents analysis of overcurrent relay settings for the selected commercial building using radial system, Library of Universiti Malaysia Pahang, Pekan Campus. The main software used is Electrical Transient and Analysis Program (ETAP) software. The analysis been done based on the real data collected from the selected commercial building which is modelled into ETAP and compared using theoretical study of manual calculation specifically for overcurrent relay settings. All the rules for the theoretical manual calculation is considered. Load flow analysis and fault analysis includes calculation of Single Line-to-Ground fault, Double Line-to-Ground fault, Lineto- Line fault and Three-Phase fault is performed using the software based on the setting obtained from the real data. The analysis is necessary as to compare the normal condition and other eleven possible conditions of circuit breakers and to ensure the stability of system. Besides, it is essential to coordinate the overcurrent relay settings by determining the main and backup protection devices for the line of fault occurs and provide correct discrimination to protect system from further damage or breakdown. Based on the analysis, it proves that the standard discrimination time between two successive relays of 0.25 seconds is practical to be used. The result shows manual calculation results are more sensitive compared to the settings made in the real commercial building. Thus, this paper is successful in determining proper and practical method on the overcurrent relay setting for power distribution network. In addition, the efficiency and reliability of the overcurrent relay coordination is validated and verified.